What can't be said paradox and contradiction in East Asian thought - Deguchi, Yasuo 1929-; Garfield, Jay L. 1955-; Priest, Graham 1948-; Sharf, Robert H. (Oxford University Press, 2021)
"Paradox drives a good deal of philosophy in every tradition. In the Indian and Western traditions, there is a tendency among many (but not all) philosophers to run from contradiction and paradox. If and when a contradiction appears in a theory, it is regarded as a sure sign that something has gone amiss. This aversion to paradox commits them, knowingly or not, to the view that reality must be consistent. In East Asia, however, philosophers have reacted to paradox differently. Many East Asian philosophers-both in the Daoist and the Buddhist traditions-have openly embraced paradox. They have taken compelling arguments for contradictory positions to suggest that the world is-at least in some respects, and often in very deep respects-inconsistent, and that our best theories of the world will therefore be inconsistent. This book is an initial survey of the writings of some influential East Asian thinkers who were committed to paradox, and for good reason. Their acceptance of contradiction allowed them to develop important insights that evaded those who consider paradox out of bounds"--
Keywords: Ideengeschichte; Widerspruch; Paradoxon; Philosophie; Ostasien; Philosophy / East Asia; Philosophy; East Asia